Odpowiedź :
Odpowiedź:
Wyjaśnienie:
NO2 -V
N2O I
NO II
NH3-III
HNO2 III
HNO3 V
Odpowiedź:
pamietaj przy przenoszeniu liczb na drugą stronę zmieniamy znak:):)
NO2 N=x O(-ll) tlenek azotu(lV)
x+ 2×(-2)=0
x+(-4)=0
x=4=> N(lV)
N2O N=x O(-ll) tlenek azotu (l)
2x+ (-2)=0
2x=2/: 2
x=1=> N(l)
NO N=x O(-ll) tlenek azotu(ll)
x+(-2)=0
x=2=> N(ll)
NH3. N=x H(l) wodorek azotu(-lll)
x+ 3×(1)=0
x+3=0
x= -3=> N(-lll)
HNO2 H(l) N=x O(-ll) kwas azotowy(lll)
(1)+ x + 2×(-2)=0
(1)+x+(-4)=0
x= 4-1=3=> N(lll)
HNO3 H(l) N=x O(-ll) kwas azotowy(V)
(1)+ x + 3×(-2)=0
(1)+x+(-6)=0
x= 6-1=5=> N(V)
Wyjaśnienie: